2021
DOI: 10.1177/00420980211005946
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the smart city through smart grids? Urban energy futures between technological experimentation and the imagined low-carbon city

Abstract: Current imaginaries of urban smart grid technologies are painting attractive pictures of the kinds of energy futures that are desirable and attainable in cities. Making claims about the future city, the socio-technical imaginaries related to smart grid developments unfold the power to guide urban energy policymaking and implementation practices. This paper analyses how urban smart grid futures are being imagined and co-produced in the city of Berlin, Germany. It explores these imaginaries to show how the polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…That way, this research is proven to have the main focus, for precise details can be seen in Figure 5. Today's imagination of urban smart grid technology paints a compelling picture of the kind of energy the future wants (Quitzow & Rohde, 2022), and this rapid development of information technology is changing the way government organizations interact with their citizens, consequently, the introduction of e-government as a critical service delivery method in the public sector (Mahmood, 2016). One of the fundamental goals of e-government is to provide institutional changes and new modalities in delivering public services to citizens (Filgueiras et al, 2019).…”
Section: The Network Between the Keyword "Corruption In Government Se...mentioning
confidence: 99%
“…That way, this research is proven to have the main focus, for precise details can be seen in Figure 5. Today's imagination of urban smart grid technology paints a compelling picture of the kind of energy the future wants (Quitzow & Rohde, 2022), and this rapid development of information technology is changing the way government organizations interact with their citizens, consequently, the introduction of e-government as a critical service delivery method in the public sector (Mahmood, 2016). One of the fundamental goals of e-government is to provide institutional changes and new modalities in delivering public services to citizens (Filgueiras et al, 2019).…”
Section: The Network Between the Keyword "Corruption In Government Se...mentioning
confidence: 99%
“…Levenda (2019) extends this argument, contending that smart grid experiments are enrolled in entrepreneurial modalities of urban governance, which seek to constrain citizen participation in urban life to the realm of individual consumption. Similarly, Quitzow and Rohde (2021) suggest that dominant narratives of the smart grid, which position this as necessary for a more sustainable, economically successful and liveable city, draw on the claims and interests of a small community of 'experts', foreclosing the development of more radical and inclusive visions of urban change.…”
Section: Theorising the Smart Gridmentioning
confidence: 99%
“…Moreover, the authors also suggested the hierarchy of input attributes from the grid stability perspective. Quitzow and Rohde (2021) have discussed the case study of Berlin for realizing a smart city through the smart grid. The authors have discussed their energy-related policies for implementing a smart city from the smart grid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quitzow and Rohde (2021) have discussed the case study of Berlin for realizing a smart city through the smart grid. The authors have discussed their energy‐related policies for implementing a smart city from the smart grid.…”
Section: Literature Reviewmentioning
confidence: 99%